Analisis Konsep Pendidikan Islam Dalam Piagam Madinah - Nurhofipah Hutabarat; Ellya Roza (Jurnal Pendidikan Islam, 2023)
The Medina Charter (shahifatul madinah), known to Muslims as the Madina constitution, is a sheet or book written by the Prophet Muhammad SAW. The purpose of this writing is to find out how to analyze the concept of Islamic education in the madinah charter. The research method uses a library research approach, which is a research conducted by collecting information and data such as books, articles and various journals related to the research title. The results of this study indicate that the presence of the Medina charter is a symbol of unity, meaning that the Medina charter can unite the people of Medina based on faith, regardless of ethnicity or class. And after the Prophet hijrah to Medina, education can be carried out freely, systematically, and structured by establishing several Islamic educational institutions. Islamic education in Medina emphasizes the formation and development of a new society, towards a social, political, and civic unity and child education in Islam. This is where Islamic education began to develop rapidly. The essence of Islamic education in this period is based on the Qur'an and Sunnah.